(untitled) (Eurasian Medical Research Periodical, 2022)
In this article, guidelines for the psychotherapy of patients with bronchial asthma and features are presented. Bronchial asthma is one of the diseases faced by many individuals and psychotherapy is used todeal with bronchial asthma which are indicated at different levels.